A visualized and scientometric analysis of research trends of weight loss in overweight/obese children and adolescents (1958–2021) - Sun, Guotao; Li, Long; Zhang, Xiaolin (Frontiers in Public Health, 2022)
Background: Weight loss is an appropriate approach to reduce the health risks associated with overweight/obese children and adolescents, and the optimal method of weight loss requires further research. This study systematically explores scientific cooperation, disciplinary interaction, hotspots and trends in the field of weight loss in overweight/obese children and adolescents (WLOCA), and provides references for further research. Methods: Citespace 5.8.R1 (64-bit) was used to conduct a comprehensive visualization analysis of the literature on WLOCA from Web of Science Core Collection, including publication, institution, country/region, author, journal, keywords and reference. Results: 2513 papers were found in the Web of Science Core Collection, and the annual number of papers published has increased significantly since 2003. Cincinnati Children’s Hospital is the institution with the largest number of publications, while Washington University plays a pivotal role in the collaboration network. In terms of nations, USA has made greater contributions than the rest by the number of publications and global cooperation research. The most influential authors in this field are Thomas H. Inge, Thomas Reinehr, Todd M. Jenkins, Epstein L. H., Ogden C. L., etc. The most active journals are "Obesity", "Intertional Journal of Obesity", "Obesity Surgery", "Pediatrics", etc. Which are characterized by interdisciplinary interactions. Research hotstopics mainly include “assessment of obesity and pathological mechanism”, “comprehensive intervention” and “bariatric surgery”, and there’s a gradual shift from “lifestyle intervention” and “pathological mechanism” to “clinical surgical application”. In addition, disciplinary integration and comprehensive research, targeted intervention and treatment, and prospective research are the future research trends. Conclusion: The overall trend in WLOCA is positive. The main contribution of this study is to reveal the overall picture of the research in this field with visual maps and detailed data by combining quantitative with qualitative approaches, which can provide valuable references for relevant researchers to quickly understand the status of studies on WLOCA, to seek cooperation, and grasp research hotspots and frontier trends.